Reactions at solid-liquid interfaces: contrasting chemistry at different crystal faces in the hydroxide-induced reactive dissolution of p-chloranil as revealed by channel flow cell voltammetry - Hill, E; Lloyd-Williams, R; Compton, R; Atherton, J (1999)
The (100), (010) and (001) faces of monoclinic crystals of the organic solid p-chloranil display contrasting reactivities towards hydrolytic dissolution induced by aqueous hydroxide ions. The differing behaviour is rationalised in terms of the functional groups exposed in the different faces.